Money never sleeps global financial markets - Films for the Humanities (Firm) (Princeton, NJ. : Films for the Humanities & Sciences, 2004)
'Money circulates through a multiplicity of financial markets at a dizzying speed and on a global scale. To make sense of the complicated world of high finance, this lively program profiles some of the people who keep the money moving'
'A presentation of Films for the Humanities & Sciences'
Keywords: International finance; Money market; Capital market; Stock exchanges; Documentary films